Estatística em um curso de administração de empresas: mobilização dos conceitos estatísticos de base - Bifi, Carlos Ricardo (2006)
Statistics has detach itself lately because it is useful in all knowledge areas Researches and studies about this subject show the necessity to deepen the knowledge about difficulties in learning teaching process including didactic aspects of this subject and mistakes made by students after this learning Our main question is to study if Administration Students learning statistics are ready to use in a competent way these notions to solve practical problems in their performance area In this research we intend to verify the mobilization knowledge level by students in college according to studies made by A Robert (1998) where he researched four analysis dimensions to teach on math The dimension number four that is our study goal studies the levels of mobilization knowledge from students We will try to diagnose in what knowledge level are students college in statistics studies reffering to tecnique mobilizável and available concepts Using activities extracted from problem situations in Administration Area and statistics knowledge can students make inter relations between the students subjects and the practical problems of their professional area